Global health emergency of monkeypox after COVID-19: A narrative review - Prachi Jain; Manu Rathee; Akanksha Gopal Shetye; S Rajesh Divakar; Sandeep Singh; Sarthak Singh Tomar (Journal of Surgical Specialties and Rural Practice, 2022)
Global hit by coronavirus is followed by another public health emergency known as monkeypox (MPX) that is a rare disease and yet has presented with sudden and wide geographic distribution. The guidelines have been released by the concerned authorities for prevention and management; however, strict measures need to be enforced so that these guidelines can be followed. Surveillance, intervention, close monitoring of the situation, and collaborative international efforts as per the guidelines can optimally aid in achieving the goal of curbing the infection spread. This article presents the current situation update of MPX infection globally and discusses the symptoms, management, and preventive measures to be followed for MPX infection.